Enhancing Nurse-Patient Communication: A Comprehensive Systematic Review Of Effective Strategies - Suraya, Citra; Tukimin bin Sansuwito; Regidor III Poblete Dioso; Aris Citra Wisuda (Journal Of Nursing Science Research, 2024)
Background: Practical communication skills are imperative in nursing to ensure patient safety and comfort. Studies reveal that nurses often fail to implement therapeutic communication fully, resulting in dissatisfaction from beginning to end patient care. Objective: This study seeks to pinpoint strategies to enhance nurses' communication proficiency with patients. Method: Employing a systematic review approach, this research delved into journals archived in the EBSCO E. Journal, Elsevier Science Direct, Pubmed, CINAHL Complete, and Google Scholar databases, alongside nursing management and leadership literature. The operational definition encapsulates the endeavors undertaken by nurses to refine communication strategies with their patients. The study was conducted across diverse clinics and hospitals, encompassing all nurses within these settings, with the research sample comprising those lacking robust communication strategies. Data was gathered through the administration of questionnaires and the utilization of observation sheets. Results: Findings underscored that training initiatives bolstered nurses' confidence in delivering comprehensive patient care. Furthermore, culturally sensitive communication skill guides proved instrumental in augmenting nurse-patient communication and patient satisfaction. Moreover, tailored therapeutic communication programs designed for pediatric nurses yielded favorable outcomes, fostering secure and healthy interactions, nurturing trust, and expediting recovery. Short workshops emerged as another effective avenue for refining nurses' communication skills. Consequently, implementing training sessions, comprehensive guides, specialized programs, and brief workshops is pivotal in elevating communication between nurses and patients.